First record of the behavior of latex drainage by Trigona spinipes (Fabricius) (Hymenoptera, Apidae) in laticiferous flowers Primeiro registro do comportamento de drenagem de latex de Trigona spinipes (Fabricius) (Hymenoptera, Apidae) em flores latescentes - Cristiana Koschnitzke (Revista Brasileira de Entomologia, 2011)
This paper describes the behavior of the bee Trigona spinipes, to avoid the latex, when piercing the base of the tubular corolla of the flowers of Mandevilla guanabarica in order to steal the nectar. Este trabalho descreve o comportamento da abelha Trigona spinipes para evitar o látex quando perfura a base da corola tubular das flores de Mandevilla guanabarica ao roubar néctar.